Probing anharmonic and heterogeneous carrier dynamics across sublattice melting in a minimal model superionic conductor - Sucharita Niyogi; Takenobu Nakamura; Genki Kobayashi; Yasunobu Ando; Takeshi Kawasaki (Proceedings of the National Academy of Sciences, 2026)
Despite decades of research, the microscopic origin of sublattice melting and fast ion transport in superionic conductors remains elusive. Here, we introduce a chemically neutral minimal binary model consisting of a rigid host lattice stabilized by short-range steric repulsion and a soft carrier sublattice interacting via long-range Wigner-type forces. This contrast naturally produces distinct melting temperatures and an intermediate sublattice-melting phase in which carriers become fluidlike while the host remains crystalline. Molecular dynamics simulations identify multiple dynamical regimes–crystalline, sublattice-melt, and fully molten–marked by sharp changes in diffusivity, structural correlations, and dynamical heterogeneity. Near sublattice melting, carrier motion is strongly anharmonic and spatially heterogeneous, beyond mean-field hopping descriptions. By tuning the density, we demonstrate that sublattice melting can be continuously controlled, establishing a direct link between lattice softness, anharmonicity, and collective ion transport. Comparison with conventional long-range Coulombic models confirms that our minimal model reproduces the key dynamical signatures of superionicity, providing a unified microscopic foundation for designing mechanically robust superionic conductors.